A Five‐Year Study of the Efficacy of Purified CD34+ Cell Therapy for Angiitis‐Induced No‐Option Critical Limb Ischemia. (30th April 2018) - Fang, Yuan; Wei, Zheng; Chen, Bin; Pan, Tianyue; Gu, Shiyang; Liu, Peng; Guo, Daqiao; Xu, Xin; Jiang, Junhao; Yang, Jue; Shi, Zhenyu; Zhu, Ting; et al.
Abstract: Angiitis‐induced critical limb ischemia (AICLI) patients constitute a remarkable proportion of no‐option critical limb ischemia (CLI) patients. Stem cell therapy has become an innovative and promising option for no‐option CLI patients. As one of these promising stem cell therapies, purified CD34+ cell transplantation (PuCeT) has shown favorable short‐term results. However, the long‐term efficacy of PuCeT has yet to be reported. This study evaluates the long‐term efficacy of PuCeT in AICLI patients. Twenty‐seven AICLI patients were enrolled from May 2009 to December 2011. Granulocyte colony‐stimulating factor (G‐CSF) and enoxaparin sodium were administered for 5 days. On day 5, CD34+ cell isolation was performed, and cells were transplanted by intramuscular injection. The primary endpoint, major‐amputation‐free survival rate (MAFS), as well as secondary endpoints, such as peak pain‐free walking time (PPFWT) and the Wong‐Baker FACES pain rating scale score (WFPRSS), were routinely evaluated during the 5‐year follow‐up period. The endpoints were as follows: the MAFS was 88.89%; PPFWT increased from 3 ± 3 to 17 ± 6 minutes; WFPRSS decreased from 7 ± 2 to 0.3 ± 1.7; the ulcer healing rate was 85.71%; the recurrence rate was 11.11%; and SF‐36v2 scores were significantly improved at 5 years after PuCeT. The rate of labor recovery 5 years after PuCeT was 65.38%, and no severe adverse effect was observed during the treatment. PuCeT demonstrated long‐term efficacy and durability as a treatment of AICLI not only in achieving limb salvage but also in recovering the labor competence and improving the quality of life of patients. Stem Cells Translational Medicine 2018;7:583–590 Abstract : Figure A, B, and C (before therapy, 3 months, and 6 months after therapy) show the ulcer healing process of a critical limb ischemia patient with Burger's disease and the efficacy of purified CD34+ cell therapy for angiitis‐induced no‐option critical limb ischemia.